Hot press formed member and manufacturing method thereof

By forming a plating layer on the substrate surface of the hot-pressed members and generating Kirkendall defects and concentrated layers, the problem of members being fragile to hydrogen embedding after thermoforming is solved, and higher hydrogen embedding resistance and corrosion resistance of the plating are achieved.

JP2025507310APending Publication Date: 2025-03-18POHANG IRON & STEEL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024546304
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-19
Filing Date
2023-04-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing hot-pressing members are vulnerable to hydrogen embedding after thermoforming, resulting in an increased risk of delayed rupture, and steel is sensitive to process parameters changes during manufacturing, resulting in uneven mechanical properties.

Method used

By forming a plating layer on the substrate surface of the hot-pressed member and generating a certain number of Kirkendall defects and concentration layers in the plating layer, the remaining diffusible hydrogen of the steel after thermoforming is reduced, thereby improving the ability to resist hydrogen embedding vulnerability.

Benefits of technology

It effectively reduces the amount of diffusible hydrogen in the members after thermoforming, improves the resistance to hydrogen embedding fragility, and enhances the corrosion resistance of the plating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507310000001_ABST
    Figure 2025507310000001_ABST
Patent Text Reader

Abstract

The present invention provides a hot press-formed member and a manufacturing method thereof, the member comprising: a base steel sheet; and a plating layer provided on at least one surface of the base steel sheet, the plating layer having an average number of Kirkendall voids per unit area within a specific range in a region within 20 μm from the interface between the base steel sheet and the plating layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot press formed member that is mainly used for automobile body parts, and a method for manufacturing the same. [Background technology]

[0002] Recently, hot press formed members are widely used in structural members of automobiles for the purpose of improving fuel efficiency by reducing the weight of the automobile and protecting passengers, etc. In particular, they can be used in bumpers, doors, filler reinforcements, etc., which require ultra-high strength or high energy absorption capacity, and a representative technology related to such hot forming technology is Patent Document 1 (U.S. Patent Publication No. 6,296,805).

[0003] In the above Patent Document 1, an Al-Si plated steel sheet is heated to 850°C or higher, and then the structure of the member is formed into martensite by hot forming using a press and rapid cooling, thereby ensuring ultra-high strength with high tensile strength. When such ultra-high strength steel for hot forming is applied, since forming is performed at high temperatures, complex shapes can be easily formed, and the increase in strength due to rapid cooling in a mold is expected to result in a weight reduction effect associated with the increased strength.

[0004] However, martensite structures are known to have low resistance to hydrogen embrittlement. In particular, parts manufactured after hot forming have residual stress due to rapid cooling after heating, and when the amount of diffusible hydrogen in the steel increases, delayed fracture due to hydrogen embrittlement is a concern, which limits the application of parts. Various studies are being conducted to overcome this drawback.

[0005] In addition, because changes in process parameters during coil manufacturing can cause changes in the overall or local mechanical properties of the sheet, a steel composition that is less sensitive to changes in specific manufacturing parameters is required to manufacture sheet with good mechanical properties and homogeneity, and delayed fracture due to hydrogen embrittlement must be prevented.In particular, because diffusible hydrogen at grain boundaries promotes the occurrence of cracks at grain boundaries when stress is generated, a method has been devised to reduce the amount of diffusible hydrogen in steel after hot press forming (or hot stepping). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] U.S. Register Publication No. 6296805 Summary of the Invention [Problem to be solved by the invention]

[0007] An embodiment of the present invention seeks to provide a hot press formed part and a method for manufacturing the same.

[0008] An embodiment of the present invention provides a hot press-formed member having excellent hydrogen embrittlement resistance and a manufacturing method thereof. More specifically, the present invention provides a hot press-formed member having excellent hydrogen embrittlement resistance after hot forming, in which a concentrated layer and Kirkendall voids are generated in a plating layer to a certain level or more, thereby reducing the amount of diffusible hydrogen remaining in the steel after hot forming, and a manufacturing method thereof.

[0009] Alternatively, still another embodiment of the present invention provides a hot press-formed member having excellent hydrogen embrittlement resistance and paint corrosion resistance, and a manufacturing method thereof.

[0010] Alternatively, one embodiment of the present invention aims to provide a hot press-formed part that is mainly used for automobile body parts, by making the diffusion rates of Al and Fe in the diffusion layer non-uniform, thereby promoting the generation of Kirkendall voids in the plating layer, thereby reducing the amount of diffusible hydrogen remaining in the steel after hot forming, and thereby providing a hot press-formed part and a manufacturing method thereof that have excellent hydrogen embrittlement resistance after hot press forming.

[0011] The object of the present invention is not limited to the above. Anyone having ordinary skill in the art to which the present invention pertains will have no difficulty in understanding further object of the present invention from the entire content of the specification of the present invention. [Means for solving the problem]

[0012] One embodiment of the present invention comprises: Base steel sheet; and The base steel sheet includes a plating layer provided on at least one surface of the base steel sheet, The above plating layer is The average number of Kirkendall voids with a major axis of 0.5 μm to 5 μm that exist within a region of 20 μm from the interface between the base steel sheet and the coating layer per unit area is 8 / 1000 μm 2 ~100 pieces / 1000μm 2 To provide a hot press-formed part that satisfies the above requirements.

[0013] Furthermore, still another embodiment of the present invention is a step of reheating a steel slab containing, by weight, C: 0.02-0.5%, Si: 0.001-2%, Al: 0.001-1%, Mn: 0.1-4%, P: 0.05% or less (excluding 0%), S: 0.02% or less (excluding 0%), N: 0.02% or less (excluding 0%), Ti: 0-0.1%, B: 0.0001-0.01%, Mo: 0-1.00%, V: 0-1.00%, Ca: 0-0.01%, Nb: 0-0.1%, W: 0-1%, REM: 0-0.3%, the balance being Fe and other unavoidable impurities, at 1050-1300°C; Finish rolling the reheated steel slab at 800-950°C to obtain a hot-rolled steel sheet; coiling the hot-rolled steel sheet at 500 to 700°C; pickling the coiled hot-rolled steel sheet so that the product of acid concentration and pickling time is 800 to 10,000 g / L*s; A step of continuously annealing the pickled steel sheet by controlling an average heating rate for each zone so as to satisfy the following formulas 1 to 3: dipping the continuously annealed steel sheet in a plating bath of aluminum or an aluminum alloy to plate it; and and a step of heat treating the plated steel sheet at Ac3 to 950° C. for 1 to 1000 seconds, followed by hot press forming. [Formula 1] 1.5℃ / s≦Zone 1 average heating rate (℃ / s)≦10.0℃ / s [Formula 2] 0.5℃ / s≦Zone 2 average heating rate (℃ / s)≦1.0℃ / s [Formula 3] 0.01℃ / s≦Zone 3 average heating rate (℃ / s)≦0.4℃ / s (In the above formula 1, zone 1 refers to the section until the surface temperature of the steel plate reaches 500°C, zone 2 refers to the section until the surface temperature of the steel plate reaches 500°C to 700°C, and zone 3 refers to the section until the surface temperature of the steel plate reaches the maximum temperature.)

[0014] One embodiment of the present invention comprises: Base steel sheet; and A plating layer provided on at least one surface of the base steel sheet; A hot press-formed member is provided that satisfies the following relational expression 2-1. [Equation 2-1] 9.5≦D B2 / D A2 <= 11.0 (In the above Relational Formula 2-1, the above D B2 is the atomic ratio of aluminum (Al) in the hot press-formed part in the range of 0.25 to 0.45. Fe / D Al The absolute value of D A2is the atomic ratio of aluminum (Al) in the hot press-formed part in the range of 0.01 to 0.2. Fe / D Al In this case, the absolute value of D Fe indicates the diffusion rate of iron (Fe), and the above D Al indicates the diffusion rate of aluminum (Al).

[0015] Furthermore, still another embodiment of the present invention is a step of reheating a steel slab containing, by weight, C: 0.02-0.5%, Si: 0.001-2%, Al: 0.001-1%, Mn: 0.1-4%, P: 0.05% or less (excluding 0%), S: 0.02% or less (excluding 0%), N: 0.02% or less (excluding 0%), Ti: 0.1% or less (including 0%), B: 0.0001-0.01%, Mo: 1.00% or less (including 0%), V: 1.00% or less (including 0%), Ca: 0.01% or less (including 0%), Nb: 0.1% or less (including 0%), W: 1% or less (including 0%), REM: 0.3% or less (including 0%), the balance being Fe and other unavoidable impurities, at 1050-1300°C; Finish rolling the reheated steel slab at 800-950°C to obtain a hot-rolled steel sheet; coiling the hot-rolled steel sheet at 500 to 700°C; pickling the coiled hot-rolled steel sheet so that the product of acid concentration and pickling time is 800 to 10,000 g / L s; A step of continuously annealing the pickled steel sheet by controlling an average heating rate for each zone so as to satisfy the following formulas 1 to 3: dipping the continuously annealed steel sheet in a plating bath of aluminum or an aluminum alloy to plate it; and The plated steel sheet is heat-treated at Ac3 to 950°C for 1 to 1000 seconds, and then hot-pressed; The present invention provides a method for producing a hot press-formed member, in which the heat treatment time range at 700°C or higher during the continuous annealing satisfies 5,000°C·s to 25,000°C·s. [Formula 1] 1.5℃ / s≦Zone 1 average heating rate (℃ / s)≦10.0℃ / s [Formula 2] 0.5℃ / s≦Zone 2 average heating rate (℃ / s)≦1.0℃ / s [Formula 3] 0.01℃ / s≦Zone 3 average heating rate (℃ / s)≦0.4℃ / s (In the above formula 1, zone 1 refers to the section until the surface temperature of the steel plate reaches 500°C, zone 2 refers to the section until the surface temperature of the steel plate reaches 500°C to 700°C, and zone 3 refers to the section until the surface temperature of the steel plate reaches the maximum temperature.) Effect of the Invention

[0016] According to one embodiment of the present invention, it is possible to provide a hot press-formed member having excellent resistance to hydrogen embrittlement and a method for manufacturing the same.

[0017] Alternatively, according to yet another embodiment of the present invention, it is possible to provide a hot press-formed member having excellent hydrogen embrittlement resistance and paint corrosion resistance, and a manufacturing method thereof.

[0018] Alternatively, according to one embodiment of the present invention, in a hot press-formed part that is mainly used for automobile body parts, the diffusion rates of Al and Fe in the diffusion layer are made non-uniform, thereby promoting the generation of Kirkendall voids in the plating layer, thereby reducing the amount of diffusible hydrogen remaining in the steel after hot forming, and it is possible to provide a hot press-formed part and a manufacturing method thereof that have excellent hydrogen embrittlement resistance after hot press forming.

[0019] The various yet significant advantages and effects of the present invention are not limited to the above, but can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]

[0020] [Figure 1]1 shows a photograph taken by a scanning electron microscope (SEM) of a cross-sectional test piece in a direction perpendicular to the rolling direction of a hot press-formed member obtained in Example 1 of the present application. [Diagram 2] 1 shows a photograph taken by a scanning electron microscope (SEM) of a cross-sectional test piece in a direction perpendicular to the rolling direction of a hot press-formed member obtained from Example 2-1, which is one embodiment of the present invention. [Diagram 3] 1 is a schematic diagram showing the range of heat treatment (i.e., the range of surface enrichment heat treatment) over time in a heat treatment section at 700° C. or higher in a continuous annealing step according to an embodiment of the present invention. [Figure 4] 1 is a schematic diagram showing a graph of InC vs. x2 in a plating layer of a hot press-formed member according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, preferred embodiments of the present invention will be described. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0022] The present inventors have found that reducing the amount of diffusible hydrogen absorbed during the heat treatment of hot press forming can suppress the induction of defects due to hydrogen delayed fracture. Specifically, during the step of heating a blank having a plating layer made of aluminum or an aluminum alloy during hot press forming, water vapor present in the heat treatment furnace is absorbed on the surface of the blank. Then, hydrogen generated by dissociation of water is absorbed in the steel while it has an austenite phase with high hydrogen solubility at high temperatures. However, when rapid cooling occurs due to hot press forming and the steel changes to a martensite phase, the solubility of hydrogen drops sharply, and the alloy plating layer formed while the plating layer is alloyed plays the role of an obstacle that makes it difficult to release hydrogen. Therefore, a considerable amount of diffusible hydrogen content remains in the steel, which increases the possibility of crack generation due to hydrogen delayed fracture. Therefore, reducing the amount of diffusible hydrogen absorbed during heat treatment is an important factor for suppressing defects.

[0023] As a result of intensive research, the inventors have confirmed that it is possible to form a certain level of Kirkendall voids in the coating layer by forming various concentrated layers on the surface of the base steel. It has been confirmed that the Kirkendall voids thus generated trap hydrogen that penetrates into the steel during hot press forming, thereby effectively preventing diffusible hydrogen from diffusing into the steel and reducing its content, and it has been determined that this can ultimately be expected to have the effect of improving hydrogen embrittlement resistance.

[0024] In addition, the inventors have found that in order to ensure hydrogen embrittlement resistance, the diffusible hydrogen content of the hot-formed parts must be 0.2 ppm to ensure excellent hydrogen embrittlement resistance, because parts with a diffusible hydrogen content of 0.2 ppm or less do not crack even when the same yield strength stress is applied to the test specimen for 120 hours to apply bending stress.

[0025] Hereinafter, a hot press-formed part according to one embodiment of the present invention will be described in detail.

[0026] According to one embodiment of the present invention, a hot press-formed member includes a base steel sheet; and a plating layer provided on at least one surface of the base steel sheet.

[0027] First, the alloy composition of the base steel sheet according to one embodiment of the present invention will be described below. It should be noted that when expressing the content of each element in the present invention, it means weight % unless otherwise specified.

[0028] Carbon (C): 0.02~0.5% by weight The C element improves the strength and hardenability of heat-treated components, and must be added appropriately as an essential element for strength adjustment. If the C content is less than 0.02%, the hardenability is low and it is difficult to ensure sufficient strength, making it difficult to apply to hot-pressed components, so 0.02% or more must be added. If the C content exceeds 0.5%, the strength increases excessively, which can cause brittleness and poor weldability, so the upper limit is preferably 0.5% or less.

[0029] Silicon (Si): 0.001 to 2% by weight The above-mentioned Si must be added as a deoxidizer in steelmaking, is a solid solution strengthening element, and is not only effective in homogenizing the internal structure as an element that inhibits the formation of carbides, but also contributes to increasing the strength of hot press formed parts and is added as an element that is effective in homogenizing material properties. However, if the content is less than 0.001%, not only cannot the above effects be expected, but excessive process costs are incurred for controlling the Si content, and if the Si content exceeds 2%, the galvanic properties are significantly reduced due to the excessive Si oxides formed on the steel sheet surface during annealing, so 2% or less is added.

[0030] Manganese (Mn): 0.1 to 4% by weight The Mn content is necessary not only to secure the desired strength by the solid solution strengthening effect, but also to suppress the formation of ferrite during hot press forming by improving hardening ability. If the Mn content is less than 0.1%, it is difficult to obtain a sufficient hardening effect, and other expensive alloy elements are excessively required due to insufficient hardening ability, which causes a problem of a large increase in manufacturing costs. In addition, if the Mn content exceeds 4%, the band-like structure arranged in the rolling direction of the fine structure deepens, causing non-uniformity in the internal structure, which may deteriorate the impact resistance, so 4% or less is added.

[0031] Phosphorus (P): 0.05% by weight or less (excluding 0%) The above-mentioned P exists as an impurity in steel, and if its maximum content exceeds 0.05%, the weldability of hot-formed parts and the material properties due to high-temperature grain boundary segregation deteriorate, so its upper limit is set to 0.05%. However, considering that it is inevitably contained as an impurity, the lower limit of the above-mentioned P content can be other than 0% or 0.5 ppm.

[0032] Sulfur (S): 0.02% by weight or less (excluding 0%) The above S is an element that, as an impurity, impairs the ductility, impact properties, and weldability of components, so the maximum content is limited to 0.02%. However, considering that it is unavoidable to include S as an impurity, the lower limit of the above S content can be other than 0% or 1 ppm.

[0033] Aluminum (Al): 0.001 to 1% by weight The above-mentioned Al is an element that, together with Si, acts as a deoxidizer during steelmaking to increase the cleanliness of steel. If the Al content is less than 0.001%, not only is it difficult to obtain the above-mentioned effect, but also excessive manufacturing process costs are incurred to control the Al content, which is undesirable. In addition, if the Al content exceeds 1%, the high-temperature ductility decreases due to the excessive AlN precipitates formed during the continuous casting process, which may cause slab cracks and lead to manufacturing problems, so the upper limit is set to 1%.

[0034] Nitrogen (N): 0.02% by weight or less (excluding 0%) The above-mentioned N is contained in the steel as an impurity. However, if the N content exceeds 0.02%, slab cracks associated with the formation of AlN are likely to occur, as with added Al, so the upper limit is set to 0.02%. However, considering that N is inevitably contained as an impurity, the lower limit of the above-mentioned N content can be other than 0% or 1 ppm.

[0035] Titanium (Ti): 0.1% or less (including 0%) The Ti combines with nitrogen remaining in the steel as an impurity to form TiN, thereby protecting B, which is used to ensure hardening, from becoming a compound. Therefore, it can be selectively added to ensure the above-mentioned effects, and the addition of Ti can be expected to provide the effects of precipitation strengthening and grain refinement through the formation of TiC precipitates. However, if the content exceeds 0.1%, a large amount of coarse TiN is formed, which deteriorates the quality of the steel, so the upper limit is set to 0.1%. Meanwhile, although not particularly limited, as an example, the lower limit of the Ti content can be 0.001%, and Ti can be selectively included in an amount of 0.001 to 0.1%.

[0036] Vanadium (B): 0.0001 to 0.01% The above-mentioned B is an element that can effectively improve hardening ability, and is an element that can segregate to the prior austenite grain boundaries to suppress the brittleness of hot-formed parts caused by the grain boundary segregation of the impurities P and / or S. However, controlling the B content to less than 0.0001% is undesirable because excessive process costs are required. Also, when the B content exceeds 0.01%, the Fe 23 The upper limit of Cr content is set at 0.01% since the formation of CB6 complex compounds may cause embrittlement during hot rolling.

[0037] Molybdenum (Mo): 1.00% or less (including 0%) The Mo element can be selectively included as an element that can effectively improve hardenability, and the upper limit of the amount of Mo added can be 1.00% in order to suppress the problem of excessive manufacturing costs. Meanwhile, although not particularly limited, as an example, the lower limit of the Mo content can be 0.001%, and Mo can be selectively included in an amount of 0.001 to 1.00%.

[0038] Vanadium (V): 1.00% or less (including 0%) The V may be optionally included as an element capable of improving hydrogen embrittlement resistance by forming carbides and reducing grain boundaries, and the upper limit of the added amount may be 1.00% in order to suppress the problem of excessive manufacturing costs. Meanwhile, although not particularly limited, as an example, the lower limit of the V content may be 0.001%, and V may be optionally included in an amount of 0.001 to 1.00%.

[0039] Calcium (Ca): 0.01% or less (including 0%) Ca may be optionally included as an element added to improve steel cleanliness by removing a certain level of P and S during steelmaking, and the upper limit of the amount of Ca added may be 0.01% in order to suppress the problem of excessive manufacturing costs. Meanwhile, although not particularly limited, as an example, the lower limit of the Ca content may be 0.001%, and Ca may be optionally included in an amount of 0.001 to 0.01%.

[0040] Niobium (Nb): 0.1% or less (including 0%) Nb can be selectively included as an element that can improve hydrogen embrittlement resistance by forming carbides and reducing grain boundaries, and the upper limit of the amount of Nb added can be 0.1% in order to suppress the problem of excessive manufacturing costs. Meanwhile, although not particularly limited, as an example, the lower limit of the Nb content can be 0.001%, and Nb can be selectively included in an amount of 0.001 to 0.1%.

[0041] Tungsten (W): 1% or less (including 0%) W can be optionally included as an element that can improve hydrogen embrittlement resistance by forming carbides to refine grain boundaries, and the upper limit of the amount of addition can be 1% in order to suppress the problem of excessive manufacturing costs. Meanwhile, although not particularly limited, as an example, the lower limit of the W content can be 0.001%, and W can be optionally included in an amount of 0.001 to 1%.

[0042] Rare earth elements (REM): 0.3% or less (including 0%) Rare earth metals (REM) are elements that may be included during steelmaking, and when the REM exceeds 0.3%, the REM may segregate excessively at grain boundaries, deteriorating hydrogen embrittlement resistance, so that REM may be selectively included in an amount of 0.3% or less. Meanwhile, although not particularly limited, as an example, the lower limit of the REM content may be 0.001%, and REM may be selectively included in an amount of 0.001 to 0.3%.

[0043] Group 1 elements: 0.005~1% by weight The base steel sheet may further contain at least one group 1 element selected from the group consisting of Sb, Sn, As, Bi, Cu and Ni, each independently in an amount of 0.005% by weight to 1% by weight.

[0044] When the above group 1 elements are added, a region where the concentration of the above group 1 elements is concentrated may exist in the coating layer of the hot press formed member from the interface between the base steel sheet and the above coating layer to the surface layer region in the lateral direction of the coating layer. As such a concentrated region of the group 1 elements is formed, it plays a role in promoting the formation of Kirkendall voids in the coating layer after hot press forming by making the diffusion speed of aluminum (Al) and iron (Fe) which diffuse mutually during high temperature heat treatment uneven. Therefore, if the content of each of the above group 1 elements is less than 0.005%, the concentrated layer is not sufficiently formed and the above-mentioned Kirkendall voids are not sufficiently generated, so it is difficult to expect an improvement effect on hydrogen embrittlement resistance. On the other hand, if the content of each of the above group 1 elements exceeds 1%, not only does the cost of the ferroalloy increase, but the generation of voids in the coating layer is excessively formed, which may cause the coating to peel off due to the stress applied during hot forming, resulting in deterioration of the corrosion resistance of the coating.

[0045] Alternatively, for the purpose of further improving the above-mentioned effects, the lower limit of the content of the group 1 element may be 0.008%, or the upper limit of the content of the group 1 element may be 0.95%.

[0046] Alternatively, according to one embodiment of the present invention, in order to further improve the above-mentioned effects, one or more elements selected from the group consisting of Sb, Sn, As and Bi may be independently contained in an amount of 0.005 to 0.1% among the group 1 elements. Alternatively, in order to further improve the above-mentioned effects, the lower limit of the content of one or more elements selected from the group consisting of Sb, Sn, As and Bi may be 0.01%, or the upper limit of the content of one or more elements selected from the group consisting of Sb, Sn, As and Bi may be 0.09%.

[0047] Furthermore, according to one embodiment of the present invention, in order to further improve the above-mentioned effects, one or more elements selected from the group consisting of Cu and Ni among the group 1 elements may be independently contained in an amount of 0.05 to 1%. Alternatively, in order to further improve the above-mentioned effects, the lower limit of the content of the one or more elements selected from the group consisting of Cu and Ni may be 0.1%, or the upper limit of the content of the one or more elements selected from the group consisting of Cu and Ni may be 0.9%.

[0048] The balance other than the above-mentioned components is iron (Fe), and there is no particular restriction on the additional addition as long as it is a component that can be contained in a steel sheet for hot press forming. In addition, since unintended impurities may be inevitably mixed in from raw materials or the surrounding environment during normal manufacturing processes, it is not possible to eliminate them. Since these impurities are known to anyone who is an engineer of normal manufacturing processes, the contents of all of them will not be mentioned in this specification.

[0049] In the present invention, the type of the plating layer is not particularly limited, and any plating layer that is conventionally applied to plated steel sheets for hot forming can be applied to the present invention without any restrictions. As an example, the plating layer can be an aluminum or aluminum alloy plating layer, and preferably, the plating layer contains 6 to 12% Si, 4% or less (including 0%) Fe, the balance being Al and other inevitable impurities.

[0050] Alternatively, as yet another example, in the case of a hot-dip plating layer, a hot-dip aluminum plating layer, a hot-dip Al-Si plating layer, a hot-dip Al-Si-Mg plating layer, a hot-dip Al-Zn plating layer, a hot-dip Al-Mg plating layer, etc. can be applied. Examples of the alloyed hot-dip plating layer include an alloyed hot-dip aluminum plating layer, an alloyed hot-dip Al-Si plating layer, an alloyed hot-dip Al-Si-Mg plating layer, an alloyed hot-dip Al-Zn plating layer, and an alloyed hot-dip Al-Mg plating layer. The plating layer may contain at least one of Mn, Cr, Cu, Mo, Ni, Sb, Sn, Ti, Ca, Sr, Mg, Be, Li, and Na. The coating weight of the plating layer is not particularly limited, and may be, for example, within a general range.

[0051] In the hot press-formed member, the average number of Kirkendall voids having a major axis of 0.5 μm to 5 μm present in a region within 20 μm from the interface between the base steel sheet and the plating layer per unit area in the plating layer is 8 voids / 1000 μm 2 ~100 pieces / 1000μm 2 Meet the following.

[0052] Kirkendall voids are formed from the interface between the base steel and the coating layer, which is generated by the addition of the above-mentioned group 1 elements and impurities, in the lateral direction of the coating layer. Among the Kirkendall voids formed in this way, Kirkendall voids of a certain size (with a major axis of 0.5 μm to 5 μm) formed in a region within 20 μm from the interface between the base steel and the coating layer reduce the amount of diffusible hydrogen that penetrates into the steel during hot press forming, thereby suppressing hydrogen embrittlement that may occur in the component after hot forming. In other words, Kirkendall voids with a major axis of less than 0.5 μm cannot effectively trap hydrogen absorbed during heat treatment for hot press forming, and have little effect on improving hydrogen embrittlement resistance. In addition, Kirkendall voids with a major axis of more than 5 μm act as defects, causing peeling of the coating, and the partial peeling of the coating during hot forming deteriorates the corrosion resistance of the coating.

[0053] As a result of intensive research, the inventors have found that excellent hydrogen embrittlement resistance and coating corrosion resistance can be ensured by setting the average number of Kirkendall voids of a certain size per unit area within an appropriate range. 2 If the density is less than 100 particles / 1000 μm, the penetration of diffusible hydrogen cannot be sufficiently prevented, and the member becomes vulnerable to hydrogen embrittlement. 2 If the thickness exceeds this value, the plating may peel off due to the stress applied during hot press forming, resulting in a problem of deterioration of the corrosion resistance of the member.

[0054] According to an embodiment of the present invention, in order to further improve the above-mentioned effects, the lower limit of the average number of the Kirkendall voids per unit area is set to 10 voids / 1000 μm 2 Or 18 pieces / 1000μm 2 It can be.

[0055] According to an embodiment of the present invention, in order to further improve the above-mentioned effects, the upper limit of the average number of the Kirkendall voids per unit area is 95 voids / 1000 μm 2 Or 92 pieces / 1000μm 2 It can be.

[0056] In addition, the above Kirkendall voids are not separately defined in this specification because the content known in the art can be similarly applied.

[0057] In this specification, the method for measuring the average number of Kirkendall voids per unit area is not particularly limited, but as an example, the measurement can be performed by observing a cross-section of the structure (e.g., a test piece taken in a direction perpendicular to the rolling direction) using a scanning electron microscope (SEM).

[0058] In this case, the interface between the base steel sheet and the coating layer can be classified by contrast difference by SEM / OM observation, but can also be classified by composition analysis by SEM-EDS, EPMA, etc. In other words, when measuring through the base steel sheet-coating layer using a line profile, etc., the interface between the base steel sheet and the coating layer can be determined at the point where the Al content is 2% by weight, and if it exceeds 2%, it can be classified as a coating layer, and if it is 2% or less, it can be classified as base steel.

[0059] On the other hand, when a parallel line is drawn 20 μm away from the interface line separating the above-mentioned base steel sheet and the plating layer in the lateral direction of the plating layer, as shown in Figure 1, the area having a black contrast existing within 20 μm of the interface 100 between the base steel sheet and the plating layer can be identified as a Kirkendall void 11.

[0060] In this specification, the major axis of the Kirkendall voids refers to the equivalent diameter of an ideal circle having the same area for each Kirkendall void.

[0061] The method for measuring the average number of Kirkendall voids per unit area is not particularly limited, and can be measured using a conventional method. 2 After taking multiple test pieces (e.g., three) with an area, 1000 μm of each test piece 2 The number of Kirkendall voids completely contained within the area is measured, and then the average value is calculated, so that the average number of Kirkendall voids per unit area can be measured. However, the number of the above-mentioned multiple test pieces is not particularly limited, as long as it is two or more.

[0062] According to one embodiment of the present invention, the base steel sheet of the hot press-formed part further contains one or more group 1 elements selected from the group consisting of Sn, As, Bi, Cu, and Ni, and can satisfy the following Relational Formula 1.

[0063]

number

[0064] (In the above Relational Formula 1, the above X coat indicates the average X content in the plating layer. max indicates the maximum content of X in the plating layer. In addition, the X indicates one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni.

[0065] The above mentioned X coat and X max is a unit indicating the content, and since it is sufficient that the units are consistent when calculating the above Relational Formula 1, the unit is not particularly limited, and may be, for example, weight percent. coat and X max The measurement method is not particularly limited.

[0066] However, for example, it can be measured by analyzing the change in the content of group 1 elements from any one point on the coating layer surface to the thickness direction of the base steel sheet side using glow discharge spectroscopy (GDS). At this time, it should be noted that the value of the above Relation 1 is satisfied for each group 1 element individually.

[0067] The average X content in the plating layer is X coat can be measured by dividing the region from the coating layer surface to the interface between the base steel sheet and the coating layer into equal intervals in the thickness direction (for example, in a direction perpendicular to the rolling direction) in the GDS profile and calculating the average value for the X content at each point. In this case, the interface between the base steel sheet and the coating layer can be determined as a point on the GDS profile where the Al content is 2 wt%.

[0068] According to an embodiment of the present invention, if the hot press formed part does not satisfy the above-mentioned Relational Formula 1, the difference in diffusion gradient between Fe and Al during hot forming may not be sufficient, and it may be difficult to sufficiently promote the formation of Kirkendall voids in the coating layer. As a result, it is difficult to achieve the effect of reducing the amount of diffusible hydrogen in steel, and it is difficult to expect the effects of the present invention to be secured.

[0069] Next, the manufacturing method of the hot-formed member will be described.

[0070] Slab Reheat First, the steel slab is reheated at 1050 to 1300°C. If the reheating temperature is less than 1050°C, the slab structure is not sufficiently homogenized, making it difficult to redissolve precipitated elements when they are used. On the other hand, if the reheating temperature is more than 1300°C, an excessive oxide layer is formed, which increases the manufacturing cost for removing the oxide layer and increases the possibility of surface defects occurring after finish rolling.

[0071] Finish rolling The reheated steel slab is finish-rolled at 800-950°C to obtain hot-rolled steel sheet. If the finish-rolling temperature is less than 800°C, two-phase rolling will proceed, ferrite will be introduced into the surface layer of the steel sheet, and it will be difficult to control the sheet shape. On the other hand, if the finish-rolling temperature exceeds 950°C, coarsening of hot-rolled grains may occur.

[0072] Winding After the finish rolling, the hot-rolled steel sheet is coiled at 500 to 700°C and cooled to produce a hot-rolled coil. If the coiling temperature is less than 500°C, martensite is formed in the entire or partial steel sheet, making it difficult to control the coil shape, and the hot-rolled steel sheet has an excessive increase in strength, which leads to poor cold rolling properties. On the other hand, if the coiling temperature exceeds 700°C, coarse carbides are excessively formed, which promotes crack generation when stress is generated in the hot-formed member, resulting in poor impact resistance.

[0073] Pickling treatment The coiled hot-rolled steel sheet is pickled so that the product of the acid concentration and the pickling time is 800 to 10,000 g / L*s. When the above-mentioned group 1 elements are added to the steel sheet that has been subjected to the above-mentioned reheating, finish rolling and coiling steps, these concentrated regions are formed in the coating layer, but when the product of the acid concentration and the pickling time is applied in the range of 800 to 10,000 g / L*s in the pickling process, the formation of the above-mentioned concentrated regions can be effectively promoted, and the effect of reducing the amount of diffusible hydrogen in the steel can be achieved.

[0074] Specifically, if the product of acid concentration and pickling time is less than 800g / L*s, scale generated during finish rolling may not be sufficiently removed, which may cause quality problems in the product. On the other hand, if the product of acid concentration and pickling time exceeds 10,000g / L*s, all or part of the concentrated area may be lost during pickling, and the expected effect may not be achieved. In addition, it may cause an increase in manufacturing costs, so the upper limit is set at 10,000g / L*s. However, if there is more than one pickling tank and the corresponding acid concentrations and pickling times are different, the above value can be expressed by adding the products of the acid concentrations and pickling times for each tank.

[0075] According to an embodiment of the present invention, the acid used in the pickling step may be any acid commonly used in the art, typically hydrochloric acid (HCl), sulfuric acid (H2SO4), etc. In particular, the use of hydrochloric acid (HCl) in the present invention has superior pickling ability, is economical in process cost, and is less likely to cause surface impurities after pickling, making it easier to ensure surface quality, compared to the use of other acids.

[0076] On the other hand, although not particularly limited, according to one embodiment of the present invention, the concentration of the acid may be in the range of 40 to 500 g / L. If the acid concentration is less than 40 g / L, the surface scale generated during hot rolling may not be sufficiently removed during the limited pickling time, and defects may occur on the surface of the steel sheet. On the other hand, if the acid concentration exceeds 500 g / L, the effect of the invention may not be achieved in the final hot press molded part due to the loss of the concentrated region, and defects in the surface layer due to over-pickling may be caused.

[0077] Also, although not particularly limited, according to one embodiment of the present invention, the pickling time may be 5 to 60 seconds (s). If the pickling time is less than 5 seconds, the surface scale of the steel sheet may not be sufficiently removed, which may cause defects on the surface, and if the pickling time exceeds 60 seconds, the concentrated region may be lost, which may reduce productivity and increase process costs.

[0078] Also, although not particularly limited, according to one embodiment of the present invention, the pickling temperature may be 40 to 120°C, and more preferably 50 to 100°C. If the pickling temperature is less than 40°C, the pickling power may be insufficient, which may adversely affect the quality of the product. On the other hand, if the pickling temperature exceeds 120°C, not only does the fixed cost for maintaining the high temperature increase, but also the amount of evaporation of the pickling solution due to the high temperature increases, which increases the cost for replenishing the lost pickling solution.

[0079] Continuous Annealing The pickled steel sheet is subjected to continuous annealing by controlling the average heating rate for each zone so as to satisfy the following formulas 1 to 3. [Formula 1] 1.5℃ / s≦Zone 1 average heating rate (℃ / s)≦10.0℃ / s [Formula 2] 0.5℃ / s≦Zone 2 average heating rate (℃ / s)≦1.0℃ / s [Formula 3] 0.01℃ / s≦Zone 3 average heating rate (℃ / s)≦0.4℃ / s (In the above formula 1, zone 1 refers to the section until the surface temperature of the steel plate reaches 500°C, zone 2 refers to the section until the surface temperature of the steel plate reaches 500°C to 700°C, and zone 3 refers to the section until the surface temperature of the steel plate reaches the maximum temperature.)

[0080] In the present invention, by performing the continuous annealing so that the average heating rate of each zone satisfies the above formulas 1 to 3 during the continuous annealing, the added group 1 elements can be effectively diffused into the coating layer region in contact with the base steel sheet, and thus the group 1 element enriched region can be effectively formed and promoted.

[0081] During the above-mentioned continuous annealing, each zone can be divided based on the surface temperature of the steel sheet. The section from the starting point (room temperature) to the temperature at which the surface temperature of the steel sheet reaches 500°C can be defined as Zone 1 (Zone 1). Next, the temperature section from 500°C to 700°C of the surface temperature of the steel sheet can be defined as Zone 2 (Zone 2). In addition, the temperature section from 700°C to the maximum annealing target temperature of the steel sheet can be defined as Zone 3 (Zone 3). That is, when the conditions from the starting point to the maximum annealing target temperature are satisfied, the group 1 elements, which are the additive elements for concentration, are sufficiently concentrated in the surface layer, and thus excellent hydrogen embrittlement resistance can be ensured after heat treatment for hot forming. Specifically, the average heating rate in zone 1 is rapidly increased, so that the time for maintaining the high temperature can be secured a little longer, and the concentrated elements can be sufficiently formed in the surface layer of the hot-pressed member after annealing because the concentrated elements diffuse quickly into the coating layer region in contact with the base steel sheet at high temperature. At this time, it should be noted that the above-mentioned zones 1 to 3 are provided sequentially in the transport direction of the steel sheet.

[0082] Meanwhile, the average heating rate in each zone can be determined by measuring the surface temperature of the steel sheet through a non-contact heat treatment temperature at the middle or end of each zone. If the steel sheet surface temperature at each measurement position and the sheet passing time according to the line speed are known, the average heating rate in each zone can be calculated backwards.

[0083] Plating The continuously annealed steel sheet is immersed in a plating bath made of aluminum or an aluminum alloy to perform plating. In this case, the plating bath can be an aluminum plating bath or an aluminum-based plating bath, for example, an Al-Si plating bath. Specifically, the hot-rolled steel sheet can be passed through a plating bath made of aluminum or an aluminum alloy after annealing to produce a plated steel sheet. In this case, the plating conditions can be applied to the present invention without any restrictions as long as they are plating conditions that are usually applied to steel sheets for hot press forming. As an example, the composition of the plating bath can include Si: 6 to 12%, Fe: 4% or less (including 0%), the balance being Al and other inevitable impurities.

[0084] At this time, although there is no particular limitation, the plating amount at the plating stage is usually 20 to 140 g / m2 on one side. 2 It is preferable to use a standard of 20 g / m 2 If the thickness is less than 140 g / m, it is difficult to ensure the desired corrosion resistance of the hot-formed parts. 2 If the amount is more than this, not only will the manufacturing cost increase due to the excessive plating adhesion, but it will also be difficult to achieve a uniform plating amount over the entire width and length of the coil.

[0085] Cold rolling According to an embodiment of the present invention, optionally, after the above-mentioned pickling treatment, the method may further include a step of cold rolling the hot-rolled steel sheet to manufacture a cold-rolled steel sheet.

[0086] Hot Press Forming A method for manufacturing a final member having excellent hydrogen embrittlement resistance and impact resistance by hot forming and die quenching using the plated steel sheet manufactured by the above-mentioned method will be described. A blank for hot forming is manufactured using the plated steel sheet manufactured by the above-mentioned steel composition and manufacturing method. The blank is heated within a temperature range of austenite single phase region temperature or higher, more specifically, Ac3 temperature or higher and 975°C or lower. If the heating temperature is lower than Ac3 temperature, it is difficult to ensure strength and impact resistance due to the presence of untransformed ferrite associated with the two-phase region. On the other hand, if the heating temperature exceeds 975°C, excessive oxides are generated on the surface of the member, making it difficult to ensure spot weldability and increasing manufacturing costs due to maintaining a high temperature. On the other hand, the Ac3 temperature may be defined in the same manner as is commonly known in the art.

[0087] The heated blank is then preferably maintained at the above temperature range for 1 to 1000 seconds. If the maintenance time is less than 1 second, it is difficult to achieve uniform temperature distribution across the blank, which may result in material deviations at different positions. On the other hand, if the maintenance time exceeds 1000 seconds, it is difficult to ensure spot weldability due to excessive oxide generation on the surface of the component, as occurs when the heating temperature is exceeded, and this not only increases the manufacturing costs of the component.

[0088] Meanwhile, although not particularly limited, according to an embodiment of the present invention, the heated blank may be transferred to a press and hot-formed and die-quenched at a cooling rate of -20°C or more. At this time, if the cooling rate is less than -20°C, a ferrite phase may be introduced during cooling and generated at grain boundaries, which may deteriorate strength and impact resistance. The steps of transferring the blank, hot press forming, and cooling are not particularly limited, and a commonly used hot press forming method may be applied as is.

[0089] Moreover, a hot press-formed member according to yet another embodiment of the present invention will be described in detail below.

[0090] The present inventors have found that reducing the amount of diffusible hydrogen absorbed during heat treatment in hot press forming can suppress the induction of defects due to hydrogen delayed fracture. Specifically, during the step of heating a blank having a plating layer made of aluminum or an aluminum alloy during hot press forming, water vapor present in a heat treatment furnace is absorbed onto the surface of the blank. Then, hydrogen generated by dissociation of water is absorbed into the steel while it has an austenite phase with high hydrogen solubility at high temperatures. However, when rapid cooling occurs due to hot press forming and the steel changes to a martensite phase, the solubility of hydrogen is rapidly reduced, and the alloy plating layer formed while the plating layer is alloyed acts as an obstacle that makes it difficult to release hydrogen.

[0091] Therefore, a significant amount of diffusible hydrogen remains in the steel, which increases the possibility of crack generation due to hydrogen delayed fracture. Therefore, reducing the amount of diffusible hydrogen absorbed during heat treatment is an important factor for suppressing defects.

[0092] As a result of intensive research, the inventors have confirmed that forming various concentrated layers on the surface of the base steel can form Kirkendall voids in the coating layer to a certain level or more. It has been confirmed that the Kirkendall voids thus formed trap hydrogen that penetrates into the steel during hot press forming, thereby effectively preventing diffusible hydrogen from diffusing into the steel and reducing its content, and it has been determined that this can ultimately be expected to have the effect of improving hydrogen embrittlement resistance.

[0093] In addition, the inventors have found that in order to ensure hydrogen embrittlement resistance, the diffusible hydrogen content of the hot-formed component must be at a level of 0.25 ppm or less in order to ensure excellent hydrogen embrittlement resistance, because a component having a diffusible hydrogen content of 0.25 ppm or less will not crack even when a bending stress is applied to a test specimen by applying the same yield strength stress for 120 hours.

[0094] According to one embodiment of the present invention, a hot press-formed member includes a base steel sheet; and a plating layer provided on at least one surface of the base steel sheet.

[0095] First, the alloy composition of an exemplary base steel sheet of the present invention will be described below, but the alloy composition of the base steel sheet is not particularly limited. It should be noted that when expressing the content of each element in the present invention, it means weight % unless otherwise specified.

[0096] Carbon (C): 0.02~0.5% by weight The C element improves the strength and hardenability of heat-treated components, and must be added appropriately as an essential element for strength adjustment. If the C content is less than 0.02%, the hardenability is low and it is difficult to ensure sufficient strength, making it difficult to apply to hot-pressed components, so 0.02% or more must be added. If the C content exceeds 0.5%, the strength increases excessively, which can cause brittleness and poor weldability, so the upper limit is set to 0.5%.

[0097] Silicon (Si): 0.001 to 2% by weight The above-mentioned Si must be added as a deoxidizer in steelmaking, is a solid solution strengthening element, and is not only effective in homogenizing the internal structure as an element that inhibits the formation of carbides, but also contributes to increasing the strength of hot press formed parts and is added as an element that is effective in homogenizing material properties. However, if the content is less than 0.001%, not only cannot the above effects be expected, but excessive process costs are incurred for controlling the Si content, and if the Si content exceeds 2%, the galvanic properties are significantly reduced due to the excessive Si oxides formed on the steel sheet surface during annealing, so 2% or less is added.

[0098] Manganese (Mn): 0.1 to 4% by weight The Mn content is necessary not only to secure the desired strength by the solid solution strengthening effect, but also to suppress the formation of ferrite during hot press forming by improving hardening ability. If the Mn content is less than 0.1%, it is difficult to obtain a sufficient hardening effect, and other expensive alloy elements are excessively required due to insufficient hardening ability, which causes a problem of a large increase in manufacturing costs. In addition, if the Mn content exceeds 4%, the band-like structure arranged in the rolling direction of the fine structure deepens, causing non-uniformity in the internal structure, which may deteriorate the impact resistance, so 4% or less is added.

[0099] Phosphorus (P): 0.05% by weight or less (excluding 0%) The above-mentioned P exists as an impurity in steel, and if its maximum content exceeds 0.05%, the weldability of hot-formed parts and the material properties due to high-temperature grain boundary segregation deteriorate, so its upper limit is set to 0.05%. However, considering that it is inevitably contained as an impurity, the lower limit of the above-mentioned P content can be other than 0% or 0.5 ppm.

[0100] Sulfur (S): 0.02% by weight or less (excluding 0%) The above S is an element that, as an impurity, impairs the ductility, impact properties, and weldability of components, so the maximum content is limited to 0.02%. However, considering that it is unavoidable to include S as an impurity, the lower limit of the above S content can be other than 0% or 1 ppm.

[0101] Aluminum (Al): 0.001 to 1% by weight The above-mentioned Al is an element that, together with Si, acts as a deoxidizer during steelmaking to increase the cleanliness of steel. If the Al content is less than 0.001%, not only is it difficult to obtain the above-mentioned effect, but also excessive manufacturing process costs are incurred to control the Al content, which is undesirable. In addition, if the Al content exceeds 1%, the high-temperature ductility decreases due to the excessive AlN precipitates formed during the continuous casting process, which may cause slab cracks and lead to manufacturing problems, so the upper limit is set to 1%.

[0102] Nitrogen (N): 0.02% by weight or less (excluding 0%) The above-mentioned N is contained in the steel as an impurity. However, if the N content exceeds 0.02%, slab cracks associated with the formation of AlN are likely to occur, as with added Al, so the upper limit is set to 0.02%. However, considering that N is inevitably contained as an impurity, the lower limit of the above-mentioned N content can be other than 0% or 1 ppm.

[0103] Titanium (Ti): 0.1% or less (including 0%) The Ti combines with nitrogen remaining in the steel as an impurity to form TiN, thereby protecting the B, which ensures hardening ability, from becoming a compound. Therefore, it can be selectively added to ensure the above-mentioned effects, and the addition of Ti can be expected to have the effects of precipitation strengthening and grain refinement through the formation of TiC precipitates. However, if the content exceeds 0.1%, a large amount of coarse TiN is formed, deteriorating the quality of the steel, so the upper limit is set to 0.1%.

[0104] Boron (B): 0.0001 to 0.01% The above-mentioned B is an element that can effectively improve hardening ability, and is an element that can segregate to the prior austenite grain boundaries to suppress the brittleness of hot-formed parts caused by the grain boundary segregation of the impurities P and / or S. However, controlling the B content to less than 0.0001% is undesirable because excessive process costs are required. Also, when the B content exceeds 0.01%, the Fe 23 The upper limit of Cr content is set at 0.01% since the formation of CB6 complex compounds may cause embrittlement during hot rolling.

[0105] Molybdenum (Mo): 1.00% or less (including 0%) The Mo element can be selectively included as an element that can effectively improve hardenability, and the upper limit of the amount of Mo added can be 1.00% in order to suppress the problem of excessive manufacturing costs.

[0106] Vanadium (V): 1.00% or less (including 0%) The V element can be selectively included as an element that can improve hydrogen embrittlement resistance by forming carbides and reducing grain boundaries, and the upper limit of the amount of V added can be 1.00% in order to suppress the problem of excessive manufacturing costs.

[0107] Calcium (Ca): 0.01% or less (including 0%) Ca may be optionally included as an element added to improve steel cleanliness by removing a certain level of P and S during steelmaking, and the upper limit of the amount of Ca added may be 0.01% to suppress the problem of excessive manufacturing costs.

[0108] Niobium (Nb): 0.1% or less (including 0%) Nb can be selectively included as an element that can improve hydrogen embrittlement resistance by forming carbides and reducing grain boundaries, and the upper limit of the amount of Nb added can be 0.1% in order to suppress the problem of excessive manufacturing costs.

[0109] Tungsten (W): 1% or less (including 0%) W can be selectively included as an element that can improve hydrogen embrittlement resistance by forming carbides to refine grain boundaries, and the upper limit of the amount of W added can be 1% in order to suppress the problem of excessive manufacturing costs.

[0110] Rare earth elements (REM): 0.3% or less (including 0%) Rare earth metals (REM) are elements that can be included during steelmaking and can be included selectively. However, if the content of rare earth elements exceeds 0.3%, REMs may segregate excessively at grain boundaries, degrading hydrogen embrittlement resistance, so the content of rare earth elements can be set to 0.3% or less.

[0111] Group 1 elements: 0.005~1% by weight The base steel sheet may further contain at least one group 1 element selected from the group consisting of Sb, Sn, As, Bi, Cu and Ni, each independently in an amount of 0.005% by weight to 1% by weight.

[0112] When the above group 1 elements are added, a region where the concentration of the above group 1 elements is concentrated may exist in the coating layer of the hot press formed member from the interface between the base steel sheet and the above coating layer to the surface layer region in the lateral direction of the coating layer. As such a concentrated region of the group 1 elements is formed, it plays a role in promoting the formation of Kirkendall voids in the coating layer after hot press forming by making the diffusion speed of aluminum (Al) and iron (Fe) which diffuse mutually during high temperature heat treatment uneven. Therefore, if the content of each of the above group 1 elements is less than 0.005%, the concentrated layer is not sufficiently formed and the above-mentioned Kirkendall voids are not sufficiently generated, so it is difficult to expect an improvement effect on hydrogen embrittlement resistance. On the other hand, if the content of each of the above group 1 elements exceeds 1%, not only does the cost of the ferroalloy increase, but the generation of voids in the coating layer is excessively formed, which may cause the coating to peel off due to the stress applied during hot forming, resulting in deterioration of the corrosion resistance of the coating.

[0113] Meanwhile, according to one embodiment of the present invention, in order to further improve the above-mentioned effects, one or more elements selected from the group consisting of Sb, Sn, As and Bi among the above group 1 elements may be independently contained in an amount of 0.005 to 0.1%.

[0114] Furthermore, according to one embodiment of the present invention, in order to further improve the above-mentioned effects, one or more elements selected from the group consisting of Cu and Ni among the above group 1 elements may be independently contained in an amount of 0.05 to 1%.

[0115] The balance other than the above-mentioned components is iron (Fe), and there is no particular restriction on the additional addition as long as it is a component that can be contained in a steel sheet for hot press forming. In addition, since unintended impurities may be inevitably mixed in from raw materials or the surrounding environment during normal manufacturing processes, it is not possible to eliminate them. Since these impurities are known to anyone who is an engineer of normal manufacturing processes, the contents of all of them will not be mentioned in this specification.

[0116] In the present invention, the type of the plating layer is not particularly limited, and any plating layer that is conventionally applied to plated steel sheets for hot forming can be applied to the present invention without any restrictions.

[0117] However, as an example, the plating layer may be an aluminum or aluminum alloy plating layer, and preferably the plating layer may contain Si: 6 to 12%, Fe: 4% or less (including 0%), the balance being Al and other unavoidable impurities.

[0118] Alternatively, as yet another example, in the case of a hot-dip plating layer, a hot-dip aluminum plating layer, a hot-dip Al-Si plating layer, a hot-dip Al-Si-Mg plating layer, a hot-dip Al-Zn plating layer, a hot-dip Al-Mg plating layer, etc. can be applied. Examples of the alloyed hot-dip plating layer include an alloyed hot-dip aluminum plating layer, an alloyed hot-dip Al-Si plating layer, an alloyed hot-dip Al-Si-Mg plating layer, an alloyed hot-dip Al-Zn plating layer, and an alloyed hot-dip Al-Mg plating layer. The plating layer may contain at least one of Mn, Cr, Cu, Mo, Ni, Sb, Sn, Ti, Ca, Sr, Mg, Be, Li, and Na. The coating weight of the plating layer is not particularly limited, and may be, for example, within a general range.

[0119] On the other hand, the hot press-formed member can satisfy the following relational expression 2-1. [Equation 2-1] 9.5≦D B2 / D A2 <= 11.0 (In the above Relational Formula 2-1, the above D B2is the atomic ratio of aluminum (Al) in the hot press-formed part in the range of 0.25 to 0.45. Fe / D Al The absolute value of D A2 is the atomic ratio of aluminum (Al) in the hot press-formed part in the range of 0.01 to 0.2. Fe / D Al In this case, the absolute value of D Fe indicates the diffusion rate of iron (Fe), and the above D Al indicates the diffusion rate of aluminum (Al).)

[0120] On the other hand, the diffusion rates (Diffusivities) of iron (Fe) and aluminum (Al) in the region where the atomic content ratio of aluminum (Al) in the hot press-formed part is 0.25 to 0.45 or in the region where the atomic content ratio of aluminum (Al) in the hot press-formed part is 0.01 to 0.2 can be determined by a conventional method known in the art using the following relational formula A, and is not particularly limited in the present invention.

[0121]

number

[0122] (In the above relational formula A, C represents the atomic content ratio of each element of iron (Fe) and aluminum (Al), A is a constant, x represents the depth (cm) in the thickness direction at a specific position from the surface of the plating layer, and D represents the diffusion rate (cm 2 / s), and t indicates time (s).

[0123] Specifically, we use the usual equation for calculating the diffusion rate (diffusivity; corresponding to "D" in the equation below) as in Equation A above, but we use the InC vs. x within the same time (i.e., under the same t conditions). 2 After determining the slope (-1 / 4 x D x t) when the graph above is plotted, the diffusion rate (D) can be calculated from the slope.

[0124] The above mentioned InC vs. x 2 An example of a graph of the diffusion rate is shown in FIG. 4. The detailed method for measuring the diffusion rate is as follows. First, glow discharge spectroscopy (GDS) is used to measure the change profile of the aluminum (Al) and iron (Fe) contents in the hot press formed part. Here, the part marked "A2" in FIG. 4 indicates the region where the atomic content ratio of aluminum (Al) is 0.01 to 0.2 (i.e., the region where the atomic % content of Al is 1 to 20%).

[0125] Moreover, the portion indicated by "B2" in FIG. 4 indicates a region where the atomic content ratio of aluminum (Al) is 0.25 to 0.45 (that is, a region where the atomic % content of Al is 25 to 45%).

[0126] In other words, after measuring the change profile of the content of each element of Al and Fe, the graphs of the Al and Fe content of InC vs. x2 in each of the parts A2 and 2 in FIG. 4 are plotted and the slopes are measured, and the diffusion rates of each element of Al and Fe in the part A2 can be obtained, and the diffusion rates of each element of Al and Fe in the part B2 can be obtained. Fe / D Al The absolute value of D B2 and D in the A2 section Fe / D Al The absolute value of D A2 By calculating the above equation 2-1, the value of D B2 / D A2 D defined by the above relational expression 2-1 can be obtained. B2 / D A2 If the value of D is less than 9.5, Kirkendall voids are not generated to a certain level or more, making it difficult to effectively trap hydrogen that penetrates during hot press forming, which may increase the amount of diffusible hydrogen in the steel and cause problems such as deterioration of the hydrogen embrittlement resistance of the component. B2 / D A2If the value exceeds 11.0, Kirkendall voids may be formed excessively, and the plating may peel off due to the stress applied during hot press forming, resulting in deterioration of corrosion resistance.

[0127] In this specification, D B2 and D. A2 means the diffusion rate at which Al and Fe diffuse into each other during heat treatment, and the above D B2 / D A2 A high value of θ can cause non-uniformity in the Fe / Al diffusion rate in the B2 and A2 parts, which can promote the formation of Kirkendall voids at the interface between the B2 and A2 parts.

[0128] Although not particularly limited, according to one embodiment of the present invention, in the above hot press-formed part, the microstructure of the base steel plate may include one or more types selected from the group consisting of martensite and bainite, or may consist of one or more types selected from the group consisting of martensite and bainite.

[0129] Although not particularly limited, according to one embodiment of the present invention, the hot press-formed member has an average number of Kirkendall voids having a diameter of 0.5 μm to 5 μm that are present in a region within 20 μm from the interface between the base steel sheet and the plating layer per unit area of ​​the plating layer of 7 voids / 1000 μm. 2 ~100 pieces / 1000μm 2 Meet the following.

[0130] Kirkendall voids are formed from the interface between the base steel and the coating layer in the lateral direction of the coating layer, which are generated by the addition of the above-mentioned group 1 elements and impurities. Among the Kirkendall voids formed in this way, Kirkendall voids of a certain size (i.e., 0.5 μm to 5 μm in diameter) formed in a region within 20 μm from the interface between the base steel and the coating layer (in the lateral direction of the coating layer) play a role in suppressing hydrogen embrittlement that may occur in the component after hot forming by reducing the amount of diffusible hydrogen that penetrates into the steel during hot press forming. That is, Kirkendall voids with a diameter of less than 0.5 μm cannot effectively trap hydrogen absorbed during heat treatment for hot press forming, and have little effect in improving hydrogen embrittlement resistance. In addition, Kirkendall voids with a diameter of more than 5 μm act as defects, causing peeling of the coating, and the partial peeling of the coating during hot forming deteriorates the corrosion resistance of the coating.

[0131] As a result of intensive research, the inventors have found that excellent hydrogen embrittlement resistance and coating corrosion resistance can be ensured by setting the average number of Kirkendall voids of a certain size per unit area within an appropriate range. 2 If the density is less than 100 particles / 1000 μm, the penetration of diffusible hydrogen cannot be sufficiently prevented, and the member becomes vulnerable to hydrogen embrittlement. 2 If the thickness exceeds this value, the plating may peel off due to the stress applied during hot press forming, resulting in a problem of deterioration of the corrosion resistance of the member.

[0132] According to an embodiment of the present invention, in order to further improve the above-mentioned effects, the lower limit of the average number of the Kirkendall voids per unit area is set to 10 voids / 1000 μm 2 Or 18 pieces / 1000μm 2 It can be.

[0133] According to an embodiment of the present invention, in order to further improve the above-mentioned effects, the upper limit of the average number of the Kirkendall voids per unit area is 95 voids / 1000 μm2 Or 92 pieces / 1000μm 2 It can be.

[0134] In addition, the above Kirkendall voids are not separately defined in this specification because the content known in the art can be similarly applied.

[0135] In this specification, the method for measuring the average number of Kirkendall voids per unit area is not particularly limited, but as an example, the measurement can be performed by observing a cross-section of the structure (e.g., a test piece taken in a direction perpendicular to the rolling direction) using a scanning electron microscope (SEM).

[0136] In this case, the interface between the base steel sheet and the coating layer can be classified by contrast difference by SEM / OM observation, but can also be classified by composition analysis by SEM-EDS, EPMA, etc. In other words, when measuring through the base steel sheet-coating layer using a line profile, etc., the interface between the base steel sheet and the coating layer can be determined at the point where the Al content is 2% by weight, and if it exceeds 2%, it can be classified as a coating layer, and if it is 2% or less, it can be classified as base steel.

[0137] On the other hand, when a parallel line is drawn 20 μm away from the interface line separating the above-mentioned base steel sheet and the coating layer in the lateral direction of the coating layer, as shown in Figure 2, a portion having a black contrast existing within a region of 20 μm from the interface between the base steel sheet and the coating layer can be identified as a Kirkendall void.

[0138] In this specification, the diameter of the Kirkendall void means the equivalent diameter of an ideal circle having the same area for each Kirkendall void.

[0139] The method for measuring the average number of Kirkendall voids per unit area is not particularly limited, and can be measured using a conventional method. 2 After taking multiple test pieces (e.g., three) with an area, 1000 μm of each test piece 2 The number of Kirkendall voids completely contained within the area is measured, and then the average value is calculated, so that the average number of Kirkendall voids per unit area can be measured. However, the number of the above-mentioned multiple test pieces is not particularly limited, as long as it is two or more.

[0140] Although not particularly limited, according to one embodiment of the present invention, in the above hot press-formed part, the base steel sheet further contains one or more group 1 elements selected from the group consisting of Sn, As, Bi, Cu and Ni (i.e., corresponding to X in the following relational formula 2-2), and the above hot press-formed part can satisfy the following relational formula 2-2.

[0141]

number

[0142] (In the above Relational Formula 2-2, the above X coat indicates the average X content in the plating layer. max indicates the maximum content of X in the plating layer. In addition, the X indicates one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni.

[0143] The above mentioned X coat and X max is a unit indicating the content, and since it is sufficient that the units are consistent when calculating the above relational formula 2-2, the unit is not particularly limited, and may be, for example, weight percent. coat and X max The measurement method is not particularly limited.

[0144] However, for example, it can be measured by analyzing the change in the content of group 1 elements from any one point on the coating layer surface to the thickness direction of the base steel sheet side using glow discharge spectroscopy (GDS). At this time, it should be noted that the value of the above Relational Formula 2-2 is satisfied for each group 1 element individually.

[0145] The average X content in the plating layer is X coat can be measured by dividing the region from the coating layer surface to the interface between the base steel sheet and the coating layer into equal intervals in the thickness direction (for example, in a direction perpendicular to the rolling direction) in the GDS profile and calculating the average value for the X content at each point. In this case, the interface between the base steel sheet and the coating layer can be determined as a point on the GDS profile where the Al content is 2 wt%.

[0146] According to one embodiment of the present invention, if the hot press-formed part does not satisfy the above-mentioned Relational Formula 2-2, the difference in diffusion gradient between Fe and Al during hot forming may not be sufficient, and it may be difficult to sufficiently promote the formation of Kirkendall voids in the coating layer, which makes it difficult to achieve the effect of reducing the amount of diffusible hydrogen in steel, and therefore makes it difficult to expect the effects of the present invention to be secured.

[0147] Next, a "method of manufacturing a hot press-formed member" according to still another embodiment of the present invention will be described.

[0148] Slab Reheat First, the steel slab is reheated at 1050 to 1300°C. If the reheating temperature is less than 1050°C, the slab structure is not sufficiently homogenized, making it difficult to redissolve precipitated elements when they are used. On the other hand, if the reheating temperature is more than 1300°C, an excessive oxide layer is formed, which increases the manufacturing cost for removing the oxide layer and increases the possibility of surface defects occurring after finish rolling.

[0149] Finish rolling The reheated steel slab is finish-rolled at 800-950°C to obtain hot-rolled steel sheet. If the finish-rolling temperature is less than 800°C, two-phase rolling will proceed, ferrite will be introduced into the surface layer of the steel sheet, and it will be difficult to control the sheet shape. On the other hand, if the finish-rolling temperature exceeds 950°C, coarsening of hot-rolled grains may occur.

[0150] Winding After the finish rolling, the hot-rolled steel sheet is coiled at 500 to 700°C and then cooled to produce a hot-rolled coil. If the coiling temperature is less than 500°C, martensite is formed in the entire or part of the steel sheet, making it difficult to control the shape of the coil, and the subsequent cold rolling properties are poor due to an excessive increase in strength of the hot-rolled steel sheet. On the other hand, if the coiling temperature exceeds 700°C, coarse carbides are excessively formed, promoting the occurrence of cracks when stress is generated in the hot-formed member, resulting in a problem of poor impact resistance.

[0151] Pickling treatment The coiled hot-rolled steel sheet is pickled so that the product of the acid concentration and the pickling time is 800 to 10,000 g / L s. When the above-mentioned group 1 elements are added to the steel sheet that has undergone the above-mentioned reheating, finish rolling and coiling steps, these concentrated regions are formed in the coating layer, but when the product of the acid concentration and the pickling time is applied in the range of 800 to 10,000 g / L s in the pickling process, the formation of the above-mentioned concentrated regions can be effectively promoted, and the effect of reducing the amount of diffusible hydrogen in the steel can be achieved.

[0152] Specifically, if the product of acid concentration and pickling time is less than 800g / L·s, scale generated during finish rolling will not be sufficiently removed, which may cause quality problems in the product. On the other hand, if the product of acid concentration and pickling time exceeds 10,000g / L·s, all or part of the concentrated area will be lost during pickling, and the expected effect will not be achieved. Not only that, but it may also cause an increase in manufacturing costs, so the upper limit is set at 10,000g / L·s. However, if there is more than one pickling tank and the acid concentrations and pickling times are different, the above value can be expressed by adding the products of the acid concentrations and pickling times for each tank.

[0153] According to an embodiment of the present invention, the acid used in the pickling step may be any acid commonly used in the art, typically hydrochloric acid (HCl), sulfuric acid (H2SO4), etc. In particular, the use of hydrochloric acid (HCl) in the present invention has superior pickling ability, is economical in process cost, and is less likely to cause surface impurities after pickling, making it easier to ensure surface quality, compared to the use of other acids.

[0154] On the other hand, although not particularly limited, according to one embodiment of the present invention, the concentration of the acid may be in the range of 40 to 500 g / L. If the acid concentration is less than 40 g / L, the surface scale generated during hot rolling may not be sufficiently removed during the limited pickling time, and defects may occur on the surface of the steel sheet. On the other hand, if the acid concentration exceeds 500 g / L, the effect of the invention may not be achieved in the final hot press molded part due to the loss of the concentrated region, and defects in the surface layer due to over-pickling may be caused.

[0155] Also, although not particularly limited, according to one embodiment of the present invention, the pickling time may be 5 to 60 seconds (s). If the pickling time is less than 5 seconds, the surface scale of the steel sheet may not be sufficiently removed, which may cause defects on the surface, and if the pickling time exceeds 60 seconds, the concentrated region may be lost, which may reduce productivity and increase process costs.

[0156] Also, although not particularly limited, according to one embodiment of the present invention, the pickling temperature may be 40 to 120°C, and more preferably 50 to 100°C. If the pickling temperature is less than 40°C, the pickling power may be insufficient, which may adversely affect the quality of the product. On the other hand, if the pickling temperature exceeds 120°C, not only does the fixed cost for maintaining the high temperature increase, but also the amount of evaporation of the pickling solution due to the high temperature increases, which increases the cost for replenishing the lost pickling solution.

[0157] Continuous Annealing The pickled steel sheet is subjected to continuous annealing by controlling the average heating rate for each zone so as to satisfy the following formulas 1 to 3. [Formula 1] 1.5℃ / s≦Zone 1 average heating rate (℃ / s)≦10.0℃ / s [Formula 2] 0.5℃ / s≦Zone 2 average heating rate (℃ / s)≦1.0℃ / s [Formula 3] 0.01℃ / s≦Zone 3 average heating rate (℃ / s)≦0.4℃ / s (In the above formula 1, zone 1 refers to the section until the surface temperature of the steel plate reaches 500°C, zone 2 refers to the section until the surface temperature of the steel plate reaches 500°C to 700°C, and zone 3 refers to the section until the surface temperature of the steel plate reaches the maximum temperature.)

[0158] In the present invention, by performing the continuous annealing so that the average heating rate of each zone satisfies the above formulas 1 to 3 during the continuous annealing, the added group 1 elements can be effectively diffused into the coating layer region in contact with the base steel sheet, and thus the group 1 element enriched region can be effectively formed and promoted.

[0159] During the above-mentioned continuous annealing, each zone can be divided based on the surface temperature of the steel sheet. The section from the starting point (room temperature) to the temperature at which the surface temperature of the steel sheet reaches 500°C can be defined as Zone 1 (Zone 1). Next, the temperature section from 500°C to 700°C of the surface temperature of the steel sheet can be defined as Zone 2 (Zone 2). In addition, the temperature section from 700°C to the maximum annealing target temperature of the steel sheet can be defined as Zone 3 (Zone 3). That is, when the conditions from the starting point to the maximum annealing target temperature are satisfied, the group 1 elements, which are the additive elements for concentration, are sufficiently concentrated in the surface layer, and thus excellent hydrogen embrittlement resistance can be ensured after heat treatment for hot forming. Specifically, the average heating rate in zone 1 is rapidly increased, so that the time for maintaining the high temperature can be secured a little longer, and the concentrated elements can be sufficiently formed in the surface layer of the hot pressed part after annealing because the concentrated elements diffuse quickly into the coating layer region in contact with the base steel sheet at high temperature. In this case, the above-mentioned zones 1 to 3 can be provided sequentially in the transport direction of the steel sheet.

[0160] Although not particularly limited, the average heating rate in each zone can be measured by measuring the surface temperature of the steel sheet through a non-contact heat treatment temperature at the middle or end of each zone. If the steel sheet surface temperature at each measurement position and the sheet passing time according to the line speed are known, the average heating rate in each zone can be calculated backwards.

[0161] On the other hand, during the continuous annealing, the range of time for heat treatment at 700°C or higher is controlled to satisfy 5,000°C·s to 25,000°C·s.

[0162] In the present invention, the pickled steel sheet must be heat-treated in the continuous annealing step so that the maximum temperature of the steel sheet exceeds 700°C, and as shown in Figure 3, the heat treatment range based on time in the range above 700°C (i.e., corresponding to the "surface enrichment heat treatment range" in Figure 3) must be in the range of 5,000°C·s to 25,000°C·s. This allows the added group 1 elements to be effectively diffused into the coating layer region in contact with the base steel sheet, thereby effectively forming and promoting the enrichment region of group 1 elements.

[0163] If the range of heat treatment times (i.e., the range of surface enrichment heat treatment) is less than 5,000°C·s, the added enrichment layer group will not be sufficiently enriched in the surface layer, and the effects of the invention, such as improved hydrogen embrittlement resistance after hot forming, may not be achieved. If the range of heat treatment times exceeds 25,000°C·s, not only will the process costs and time for continuous annealing increase, but the galvanic properties may deteriorate, resulting in uneven plating or missing plating.

[0164] Plating The continuously annealed steel sheet can be plated, for example, by immersing it in a plating bath made of aluminum or an aluminum alloy. In this case, the plating bath can be an aluminum plating bath or an aluminum-based plating bath, for example, an Al-Si plating bath. Specifically, the hot-rolled steel sheet can be passed through a plating bath made of aluminum or an aluminum alloy after annealing to produce a plated steel sheet. In this case, the plating conditions can be applied to the present invention without any restrictions as long as they are plating conditions that are usually applied to steel sheets for hot press forming. For example, the composition of the plating bath can include Si: 6 to 12%, Fe: 4% or less (including 0%), the balance being Al and other inevitable impurities.

[0165] At this time, although there is no particular limitation, the plating amount at the plating stage is usually 20 to 140 g / m2 on one side. 2 It can be set to 20g / m2 on one side. 2If the thickness is less than 140 g / m, it may be difficult to ensure the desired corrosion resistance of the hot-formed parts. 2 If the amount is more than this, not only will the manufacturing cost increase due to the excessive plating adhesion, but it may also be difficult to achieve a uniform plating amount in the entire width and length directions of the coil.

[0166] Cold rolling According to an embodiment of the present invention, optionally, after the above-mentioned pickling treatment, the method may further include a step of cold rolling the hot-rolled steel sheet to manufacture a cold-rolled steel sheet.

[0167] Hot Press Forming A method for manufacturing a final member having excellent hydrogen embrittlement resistance and crash resistance by hot forming and die quenching using the plated steel sheet manufactured by the above-mentioned method will be described. A blank for hot forming is manufactured using the plated steel sheet manufactured by the above-mentioned steel composition and manufacturing method. The blank is heated at a temperature range of austenite single phase region temperature or higher, more specifically, Ac3 temperature or higher and 975°C or lower. If the heating temperature is lower than Ac3 temperature, it is difficult to ensure strength and crash resistance due to the presence of untransformed ferrite associated with the two-phase region. On the other hand, if the heating temperature exceeds 975°C, excessive oxides are generated on the surface of the member, making it difficult to ensure spot weldability and increasing manufacturing costs due to maintaining a high temperature. On the other hand, the Ac3 temperature is not separately defined in this specification because the definition commonly known in the art can be applied in the same way.

[0168] The heated blank is then preferably maintained at the above temperature range for 1 to 1,000 seconds. If the maintenance time is less than 1 second, it is difficult to achieve uniform temperature distribution across the blank, which may result in material deviations at different positions. On the other hand, if the maintenance time exceeds 1,000 seconds, it is difficult to ensure spot weldability due to excessive oxide generation on the component surface as occurs when the heating temperature is exceeded, and this not only increases the manufacturing costs of the component.

[0169] Meanwhile, although not particularly limited, according to an embodiment of the present invention, the heated blank may be transferred to a press and hot-formed and die-quenched at a cooling rate of 20° C. / s or more. At this time, if the cooling rate is less than 20° C. / s, a ferrite phase may be introduced during cooling and generated at grain boundaries, which may deteriorate strength and impact resistance. The steps of transferring the blank, hot press forming, and cooling are not particularly limited, and a commonly used hot press forming method may be applied as is. EXAMPLES

[0170] The present invention will be described in more detail below with reference to examples. However, it should be noted that the following examples are intended to illustrate and embody the present invention, and are not intended to limit the scope of the present invention, since the scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.

[0171] (Experimental Example 1) The composition by weight was 0.22%C-0.2%Si-1.2%Mn-0.03%Al-0.01%P-0.002%S-0.03%Ti-0.004%N, and additional elements of group 1 were added as shown in Table 1 below. A steel slab with a thickness of 40 mm was produced by vacuum melting.

[0172] The slab was maintained at 1200°C for 1 hour, hot rolled to a hot rolling end temperature of 900°C, and coiled to a coiling temperature of 600°C. Then, cold rolling including a pickling process was performed. Then, the cold-rolled steel sheet obtained by cold rolling was sequentially subjected to pickling, continuous annealing, and plating. At this time, pickling conditions within the scope of the present invention and continuous annealing conditions for each zone were applied, and more specifically, HCl concentration*pickling time was 4,000g / L*s (however, the HCl concentration was 200g / L and the pickling time was 20 seconds, and the pickling temperature was 80°C, which was applied collectively), and the annealing conditions for each zone were applied collectively as follows: Formula (1): 3.0°C / s, Formula (2): 0.5°C / s, and Formula (3): 0.3°C / s.

[0173] Then, the plate was immersed in a plating bath consisting of Al-9%Si-2%, Fe, and the balance being a trace amount of impurities, and plated. In this example, a temperature of 930°C and a heating time of 6 minutes were applied, followed by a transfer time to a die of 10 seconds, followed by hot forming and die quenching.

[0174] In order to confirm whether the enriched layer was sufficiently formed on the surface of the substrate layer in the test specimens manufactured as described above, the contents of group 1 elements listed in Table 1 were analyzed by glow discharge spectrometry (GDS) using GDS850A (model name, manufactured by LECO), DC and RF equipment.

[0175] Referring to the above GDS analysis results, X for each group 1 element max and X coat The weight percent content was measured, and the ratio was calculated, and the results are shown in Table 1 below.

[0176] Then, in order to confirm Kirkendall voids within 20 μm in the plating layer direction in the plating layer, a cross section of the structure (a test piece was taken in a direction perpendicular to the rolling direction) was observed using an electron microscope (SEM, Scanning Electron Microscopy). Using the photograph thus observed, a magnification of 1000 was applied and a photograph was taken, and as shown in FIG. 1 (measured for the hot press-formed member obtained from Example 1), the parts having black contrast present within the range can be identified as Kirkendall voids. After applying this magnification and surrounding a rectangle of 20 μm thickness × 50 μm length, the average number of Kirkendall voids confirmed within the range was measured and calculated as number / 1000 μm. 2 The results are shown in Table 1.

[0177] To evaluate the amount of diffusible hydrogen for materials with various Kirkendall voids, a TDA (Thermal Desorption Analysis) device (Bruker G8: model name) was used to measure. The conditions for analyzing the amount of diffusible hydrogen were to raise the temperature to 400℃ at 20℃ / min, maintain the time so that the diffusible hydrogen peak appears sufficiently, and measure the diffusion hydrogen curve. The total amount of diffusible hydrogen in the steel was calculated by integrating this curve, and the results are shown in Table 1.

[0178] In order to understand the effect of Kirkendall voids in the plating layer on the corrosion resistance of the coating, a scribe of w0.5 × L50mm was formed, and a corrosion resistance test according to the VDA233-102 standard was performed for 10 cycles, after which the peel width of the corroded area around the scribe was measured according to the ISO4628-8 standard. At this time, if the measured peel width was 2.5mm or less, it was rated as "good", and if it exceeded 2.5mm, it was rated as "poor", as shown in Table 1 below.

[0179] [Table 1]

[0180] As shown in Table 1, the amount of diffusible hydrogen changed as the average number per unit area of ​​Kirkendall voids with major axes of 0.5 μm to 5 μm that exist within a region of 20 μm from the interface between the base steel sheet and the coating layer changed.

[0181] At this time, in the coating layer, the average number per unit area of ​​Kirkendall voids having a major axis of 0.5 μm to 5 μm present in a region within 20 μm from the interface between the base steel sheet and the coating layer is 8 / 1000 μm 2 ~100 pieces / 1000μm 2 In the case of Examples 1 to 18, which satisfy the above condition, the amount of diffusible hydrogen in the hot press formed parts is 0.2 ppm or less, and it can be confirmed that the hydrogen embrittlement resistance is excellent and the coating corrosion resistance is good.

[0182] On the other hand, in the above-mentioned Examples 1 to 18, the average number per unit area of ​​Kirkendall voids having a major axis of 2 μm to 6 μm present in the region within 20 μm from the interface between the base steel sheet and the above-mentioned coating layer was 10 voids / 1000 μm. 2 ~100 pieces / 1000μm 2 It was also confirmed that the following points were satisfied.

[0183] On the other hand, the average number of Kirkendall voids with a major axis of 0.5 μm to 5 μm present in the region within 20 μm from the interface between the base steel sheet and the coating layer per unit area is 8 voids / 1000 μm 2 In the cases of Comparative Examples 1, 3, 5, 7, 9, and 11, where the hydrogen content was less than 0.2 ppm, the hydrogen absorbed during hot press forming could not be accurately trapped, and the amount of diffusible hydrogen exceeded 0.2 ppm, making it difficult to ensure hydrogen embrittlement resistance.

[0184] In addition, even if the composition of the present invention is satisfied, the average number of Kirkendall voids per unit area having a major axis of 0.5 μm to 5 μm present in a region within 20 μm from the interface between the base steel sheet and the coating layer is 100 voids / 1000 μm 2 In the case of Comparative Examples 2, 4, 6, 8, 10, and 12, where the amount of diffusible hydrogen exceeded 100%, the amount of diffusible hydrogen was reduced. However, the bonding strength of the plating layer interface was weakened due to the formation of excessive Kirkendall voids, and a phenomenon occurred in which a part of the plating layer peeled off during hot forming or paint scribing, which excessively deteriorated the corrosion resistance of the coating and caused defects.

[0185] (Experimental Example 2) The composition of the steel used in the present invention is 0.22%C-0.25%Si-1.25%Mn-0.2%Cr-0.03%Al-0.01%P-0.002%S-0.03%Ti-0.0025%B-0.004%N. As shown in Table 2 below, various group 1 element contents were added to the base steel sheet, and slabs having each composition were manufactured through vacuum melting with a thickness of 40 mm. After maintaining the temperature at 1200°C for 1 hour, the slab was hot rolled to a hot rolling finish temperature of 900°C and coiled to a coiling temperature of 600°C. Then, the cold-rolled steel sheet obtained by cold rolling was sequentially subjected to pickling, continuous annealing, and plating. In this case, pickling conditions and continuous annealing conditions for each zone within the scope of the present invention were applied. More specifically, the HCl concentration and pickling time were 4,000 g / L s (however, the HCl concentration was 200 g / L, the pickling time was 20 seconds, and the pickling temperature was 80° C., all of which were applied), and the annealing conditions for each zone were 3.0° C. / s for Zone 1, 0.5° C. / s for Zone 2, and 0.3° C. / s for Zone 3, all of which were applied.

[0186] The plating was performed by immersing the steel sheet in a plating bath consisting of Al-9%Si-2%Fe with the balance being a trace amount of impurities.

[0187] Thereafter, the mixture was heat-treated at Ac3 to 950°C and then hot press-molded. The heating time was 6 minutes, the transfer time to the mold was 10 seconds, and then die quenching was applied.

[0188] To confirm Kirkendall voids within 20μm in the plating layer direction in the plating layer, a scanning electron microscope (SEM) was used to observe the cross section of the structure (a test piece was taken in a direction perpendicular to the rolling direction). Using the photograph thus observed, a magnification of 1000 was applied and measurements were taken on the hot press formed parts), and as shown in the figure, the areas with black contrast present within the range can be identified as Kirkendall voids. This magnification was applied to surround a rectangle of 20μm thickness x 50μm length, and the average number of Kirkendall voids confirmed within that range was measured and calculated as number / 1000μm. 2 The results are shown in the table.

[0189] To evaluate the amount of diffusible hydrogen for materials with various Kirkendall voids, a TDA (Thermal Desorption Analysis) device (Bruker G8: model name) was used to measure. The amount of diffusible hydrogen was measured 3 days after hot forming heat treatment, and the conditions for analyzing the amount of diffusible hydrogen were to raise the temperature to 400℃ at 20℃ / min, maintain the time so that the diffusible hydrogen peak appears sufficiently, and measure the diffusion hydrogen curve. The total amount of diffusible hydrogen in the steel can be calculated by integrating this curve, and the results are shown in the table.

[0190] To evaluate hydrogen embrittlement resistance, a bending stress was applied to a test piece measuring 14.5 mm in width and 73 mm in length. A strain of 0.7% was applied to the outermost turn of the test piece, and the test piece was then immersed in 0.1N hydrochloric acid. The time to fracture was measured and a test piece was rated as good if it did not fracture after 120 hours or more, and a test piece that fractured in less than 120 hours was rated as poor.

[0191] In order to confirm whether the enriched layer was sufficiently formed on the surface of the substrate layer in the test specimens manufactured as described above, the contents of group 1 elements listed in Table 2 were analyzed by glow discharge spectrometry (GDS) using GDS850A (model name, manufactured by LECO), DC and RF equipment.

[0192] In addition, to evaluate the adhesion of electrodeposition coating, the ISO2409 standard was applied, a 10x10 (1mm wide) grid was applied to the coated surface with a blade, and an adhesion test tape was placed parallel to the grid pattern and attached, then peeled off and the area of ​​the peeled coating layer was observed using a magnifying glass. In this case, separation of less than 5% of the grid area was evaluated as good, and separation of more than 5% was evaluated as poor, and these are shown in Table 2 below.

[0193] [Table 2]

[0194] As can be seen from the results in Table 2, in the case of Examples 2-1 to 2-12 which satisfy the relational formula 2-1 according to the present invention, it was confirmed that not only the amount of diffusible hydrogen was reduced and the resistance to hydrogen embrittlement was excellent, but also the electrodeposition coating adhesion was excellent.

[0195] On the other hand, in the case of Comparative Examples 2-1 to 2-15 which do not satisfy the relational formula 2-1, it was confirmed that at least one of the hydrogen embrittlement resistance and the electrodeposition coating adhesion was deteriorated compared to the examples.

[0196] On the other hand, although not particularly limited, in the case of Examples 2-2, 2-3, 2-5, 2-6, 2-8, 2-9, 2-11, and 2-12, the average number of Kirkendall voids per unit area having a diameter of 2 μm to 6 μm present in a region within 20 μm in the lateral direction of the coating layer from the interface between the base steel sheet and the coating layer was 10 voids / 1000 μm 2 ~100 pieces / 1000μm 2 Also, referring to the GDS analysis results, X for each group 1 element was max and Xcoat When the weight percent content was measured, it was confirmed that the above-mentioned Examples 2-2, 2-3, 2-5, 2-6, 2-8, 2-9, 2-11, and 2-12 satisfied the relational formula 2-2. [Explanation of symbols]

[0197] 11 Kirkendall Boyd 100 Interface between base steel sheet and coating layer

Claims

1. Base steel sheet; and The base steel sheet includes a plating layer provided on at least one surface of the base steel sheet, The plating layer is The average number of Kirkendall voids having a major axis of 0.5 μm to 5 μm present in a region within 20 μm from the interface between the base steel sheet and the coating layer per unit area is 8 / 1000 μm 2 ~100 pieces / 1000μm 2 Hot press formed parts that meet the above requirements.

2. The average number of Kirkendall voids per unit area is 10 / 1000 μm 2 ~95 pieces / 1000μm 2 The hot press-formed member according to claim 1 , which satisfies the above.

3. The average number of Kirkendall voids per unit area is 18 / 1000 μm 2 ~92 pieces / 1000μm 2 The hot press-formed member according to claim 1 , which satisfies the above.

4. The base steel sheet contains, by weight, C: 0.02 to 0.5%, Si: 0.001 to 2%, Al: 0.001 to 1%, Mn: 0.1 to 4%, P: 0.05% or less (excluding 0%), S: 0.02% or less (excluding 0%), N: 0.02% or less (excluding 0%), Ti: 0.1% or less (including 0%), B: 0.0001 to 0.01%, Mo: 1.00% or less (including 0%), V: 1.00% or less (including 0%), Ca: 0.01% or less (including 0%), Nb: 0.1% or less (including 0%), W: 1% or less (including 0%), REM: 0.3% or less (including 0%), the balance Fe and other inevitable impurities. The hot press formed member according to claim 1.

5. The hot press-formed member according to claim 1, wherein the base steel sheet further contains one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni, each independently at 0.005 to 1 wt%.

6. The base steel sheet further contains one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni, Among the group 1 elements, one or more elements selected from the group consisting of Sb, Sn, As and Bi are each independently contained in an amount of 0.005 to 0.1%; The hot press formed member according to claim 1, wherein the first group of elements independently contains 0.05 to 1% of one or more elements selected from the group consisting of Cu and Ni.

7. The base steel sheet further contains one or more group 1 elements selected from the group consisting of Sn, As, Bi, Cu, and Ni, The hot press-formed member according to claim 1 , which satisfies the following relational expression 1: [0010] (In the above-mentioned Relational Formula 1, the X coat indicates the average X content in the plating layer, and the unit is weight percent. max indicates the maximum content of X in the plating layer, the unit is weight %, and the X indicates one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni.

8. The plating layer has an average number of Kirkendall voids having a major axis of 2 μm to 6 μm that exist in a region within 20 μm from the interface between the base steel sheet and the plating layer per unit area of ​​10 voids / 1000 μm 2 ~100 pieces / 1000μm 2 The hot press-formed member according to claim 1 , which satisfies the above.

9. reheating the steel slab containing, by weight, C: 0.02-0.5%, Si: 0.001-2%, Al: 0.001-1%, Mn: 0.1-4%, P: 0.05% or less (excluding 0%), S: 0.02% or less (excluding 0%), N: 0.02% or less (excluding 0%), Ti: 0.1% or less (including 0%), B: 0.0001-0.01%, Mo: 1.00% or less (including 0%), V: 1.00% or less (including 0%), Ca: 0.01% or less (including 0%), Nb: 0.1% or less (including 0%), W: 1% or less (including 0%), REM: 0.3% or less (including 0%), the balance being Fe and other inevitable impurities, at 1050-1300°C; Finish rolling the reheated steel slab at 800-950°C to obtain a hot-rolled steel sheet; coiling the hot-rolled steel sheet at 500 to 700°C; pickling the coiled hot-rolled steel sheet so that the product of the acid concentration and the pickling time is 800 to 10,000 g / L*s; A step of continuously annealing the pickled steel sheet by controlling an average heating rate for each zone so as to satisfy the following formulas 1 to 3: dipping the continuously annealed steel sheet in a plating bath of aluminum or an aluminum alloy to plate it; and heat treating the plated steel sheet at Ac3 to 950° C. for 1 to 1000 seconds, and then hot press forming the plated steel sheet. [Formula 1] 1.5° C. / s≦Average heating rate (° C. / s) of Zone 1≦10.0° C. / s [Formula 2] 0.5° C. / s≦Average heating rate (° C. / s) of zone 2≦1.0° C. / s [Formula 3] 0.01° C. / s≦Average heating rate (° C. / s) of zone 3≦0.4° C. / s (In the above formula 1, zone 1 refers to a section until the surface temperature of the steel plate reaches 500°C, zone 2 refers to a section until the surface temperature of the steel plate reaches 500°C to 700°C, and zone 3 refers to a section until the surface temperature of the steel plate reaches the maximum temperature.)

10. Base steel sheet; and a plating layer provided on at least one surface of the base steel sheet; A hot press-formed member that satisfies the following relational formula 2-1. [Relationship 2-1] 9.5≦D B2 / D A2 ≦11.0 (In the above-mentioned Relational Formula 2-1, the above-mentioned D B2 is the D in the region where the atomic content ratio of aluminum (Al) in the hot press formed part corresponds to 0.25 to 0.45 Fe / D Al The absolute value of D A2 is the D in the region where the atomic content ratio of aluminum (Al) in the hot press formed part corresponds to 0.01 to 0.2 Fe / D Al In this case, the absolute value of D Fe represents the diffusion rate of iron (Fe), and Al indicates the diffusion rate of aluminum (Al).

11. The hot press-formed member according to claim 10, wherein the microstructure of the base steel sheet is at least one selected from the group consisting of martensite and bainite.

12. The average number of Kirkendall voids having a diameter of 0.5 μm to 5 μm that exist in a region within 20 μm in the lateral direction of the coating layer from the interface between the base steel sheet and the coating layer per unit area is 7 / 1000 μm 2 ~100 pieces / 1000μm 2 The hot press-formed member according to claim 10,

13. The average number of Kirkendall voids per unit area is 10 / 1000 μm 2 ~95 pieces / 1000μm 2 The hot press-formed part according to claim 12,

14. The average number of Kirkendall voids per unit area is 18 / 1000 μm 2 ~92 pieces / 1000μm 2 The hot press-formed part according to claim 12,

15. The base steel sheet contains, by weight, C: 0.02 to 0.5%, Si: 0.001 to 2%, Al: 0.001 to 1%, Mn: 0.1 to 4%, P: 0.05% or less (excluding 0%), S: 0.02% or less (excluding 0%), N: 0.02% or less (excluding 0%), Ti: 0.1% or less (including 0%), B: 0.0001 to 0.01%, Mo: 1.00% or less (including 0%), V: 1.00% or less (including 0%), Ca: 0.01% or less (including 0%), Nb: 0.1% or less (including 0%), W: 1% or less (including 0%), REM: 0.3% or less (including 0%), the balance Fe and other inevitable impurities. The hot press formed member according to claim 10.

16. The base steel sheet contains one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu and Ni, each independently in an amount of 0.005% by weight to 1% by weight. The hot press-formed member according to claim 10.

17. The base steel sheet contains one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni, Among the group 1 elements, one or more elements selected from the group consisting of Sb, Sn, As and Bi are each independently contained in an amount of 0.005 to 0.1%; The hot press formed member according to claim 10, wherein the first group of elements independently contains 0.05 to 1% of one or more elements selected from the group consisting of Cu and Ni.

18. The base steel sheet further contains one or more group 1 elements selected from the group consisting of Sn, As, Bi, Cu, and Ni, The hot press molded member according to claim 10, which satisfies the following relational formula 2-2. [0025] (In the above-mentioned Relational Formula 2-2, the above-mentioned X coat indicates the average X content in the plating layer, and the unit is weight percent. max indicates the maximum content of X in the plating layer, the unit is weight %, and the X indicates one or more group 1 elements selected from the group consisting of Sb, Sn, As, Bi, Cu, and Ni.

19. The plating layer has an average number of Kirkendall voids having a diameter of 2 μm to 6 μm that are present in a region within 20 μm in a lateral direction of the plating layer from the interface between the base steel sheet and the plating layer of 10 / 1000 μm 2 ~100 pieces / 1000μm 2 The hot press-formed member according to claim 10,

20. reheating the steel slab containing, by weight, C: 0.02-0.5%, Si: 0.001-2%, Al: 0.001-1%, Mn: 0.1-4%, P: 0.05% or less (excluding 0%), S: 0.02% or less (excluding 0%), N: 0.02% or less (excluding 0%), Ti: 0.1% or less (including 0%), B: 0.0001-0.01%, Mo: 1.00% or less (including 0%), V: 1.00% or less (including 0%), Ca: 0.01% or less (including 0%), Nb: 0.1% or less (including 0%), W: 1% or less (including 0%), REM: 0.3% or less (including 0%), the balance being Fe and other inevitable impurities, at 1050-1300°C; Finish rolling the reheated steel slab at 800-950°C to obtain a hot-rolled steel sheet; coiling the hot-rolled steel sheet at 500 to 700°C; pickling the coiled hot-rolled steel sheet so that the product of acid concentration and pickling time is 800 to 10,000 g / L·s; A step of continuously annealing the pickled steel sheet by controlling an average heating rate for each zone so as to satisfy the following formulas 1 to 3: dipping the continuously annealed steel sheet in a plating bath of aluminum or an aluminum alloy to plate it; and heat treating the plated steel sheet at Ac3 to 950°C for 1 to 1000 seconds, and then hot press forming the plated steel sheet; The method for producing a hot press-formed member, wherein during the continuous annealing, the heat treatment time range at 700 ° C. or higher satisfies 5,000 ° C. s to 25,000 ° C. s. [Formula 1] 1.5° C. / s≦Average heating rate (° C. / s) of Zone 1≦10.0° C. / s [Formula 2] 0.5° C. / s≦Average heating rate (° C. / s) of zone 2≦1.0° C. / s [Formula 3] 0.01° C. / s≦Average heating rate (° C. / s) of zone 3≦0.4° C. / s (In the above formula 1, zone 1 refers to a section until the surface temperature of the steel plate reaches 500°C, zone 2 refers to a section until the surface temperature of the steel plate reaches 500°C to 700°C, and zone 3 refers to a section until the surface temperature of the steel plate reaches the maximum temperature.)

Citation Information

Patent Citations

  • Fe-Al PLATED HOT-STAMPED MEMBER AND METHOD FOR PRODUCING Fe-Al PLATED HOT-STAMPED MEMBER

    WO2019160106A1

  • Coated steel sheet with thin aluminum alloy coating and coating method therefor

    WO2021248635A1

  • Coated hot- and cold-rolled steel sheet comprising a very high resistance after thermal treatment

    US6296805B1